2009
DOI: 10.1152/ajpheart.00100.2009
|View full text |Cite
|
Sign up to set email alerts
|

ERK phosphorylation mediates sildenafil-induced myocardial protection against ischemia-reperfusion injury in mice

Abstract: Sildenafil, a selective inhibitor of phosphodiesterase type 5, induces powerful protection against myocardial ischemia-reperfusion injury through activation of cGMP-dependent protein kinase (PKG). We further hypothesized that PKG-dependent activation of survival kinase ERK may play a causative role in sildenafil-induced cardioprotection via induction of endothelial nitric oxide synthase (eNOS)/inducible nitric oxide synthase (iNOS) and Bcl-2. Our results show that acute intracoronary infusion of sildenafil in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 29 publications
5
100
0
1
Order By: Relevance
“…For example, evidence shows that PKG can protect cells from IR injury by activating signaling cascades that delay mPTP opening [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence shows that PKG can protect cells from IR injury by activating signaling cascades that delay mPTP opening [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…2). Several previous studies have shown that activated ERK1/2 mediates protection against I/R injury (11,18). Moreover, mice expressing an unphosphorylatable (S1179A) form of eNOS show more severe infarction than wild-type mice (1).…”
Section: Discussionmentioning
confidence: 99%
“…PKG-I is expressed in vascular smooth muscle cells, cardiomyocytes, endothelial cells, mesangial cells, renal tubular cells, macrophages, and other cell types (9). Recent studies demonstrated the protective effect of the cGMP/PKG signaling pathway on IR injury in the heart as well as in cardiomyocytes through several mechanisms such as regulation of mitochondria K ATP channels or enhanced phosphorylation of Akt, ERK, and glycogen synthase kinase (GSK)-3␤ (5,11,13) . However, whether PKG displays a protective effect on kidney IR injury is unknown.…”
mentioning
confidence: 99%